• Matéria: Matemática
  • Autor: laraklauberg14
  • Perguntado 9 anos atrás

7p + 15 - 5p 10= -17 + 13p

Respostas

respondido por: lucasrodrigues24
2
7p - 5p -13p = -10 -15 -17                                                                                     11p = 42                                                                                                          p = 42/11                                                                                                           p = 3.81
respondido por: hainabaschirotto
1

Resposta: -42

Explicação passo-a-passo:

7p+15-5p 10 = -17+13p

7p-5p-13p = -17-15-10

2p-13p = -32-10

11p = -42

     

Perguntas similares